A method for purifying an electronic grade polyol compound
Patent Information
- Application Number
- CN202610963343.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这类树脂对已经与多元醇形成稳定螯合物的金属离子去除效果较差,难以将金属离子浓度降至ppb级别
1、极高的除金属效率:本发明的功能化树脂带有膦酸基和硫醇基,能有效捕获已与多元醇形成螯合物的金属离子,最终产品中的单一金属离子含量可稳定控制在1 ppb以下,能够满足当下先进半导体工艺的严苛要求。
Smart Images

Figure CN123003376A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electronic-grade chemical purification, specifically relating to a method for purifying electronic-grade polyol compounds. Background Technology
[0002] Polyols, such as ethylene glycol (EG), propylene glycol (PG), and glycerol, play an indispensable role in many industrial fields due to their excellent physicochemical properties (e.g., high boiling point, low volatility, and good solubility). Especially in the semiconductor and microelectronics industries, high-purity polyols are key materials in the manufacturing process, widely used as solvents for photoresists, components of chip cleaning solutions, additives in etching solutions, and media in cooling systems.
[0003] As the feature size of semiconductor integrated circuits continues to shrink, the purity requirements for all chemicals used in the manufacturing process have reached unprecedented levels. Among these chemicals, metal ions and moisture are two of the most critical impurities. Metal ions, especially alkali metals (such as sodium hydroxide), are particularly problematic. + K + ), alkaline earth metals (Ca 2+ Mg 2+ ) and transition metals (Fe 3+ Cu 2+ Ni 2+ Zn 2+ Even trace amounts of metallic impurities can have a fatal impact on the performance and reliability of semiconductor devices. For example, alkali metal ions are mobile charges that can reduce the insulation performance of the gate oxide layer and change the threshold voltage of the transistor; transition metal ions may form metal silicides on the silicon wafer surface, leading to leakage, short circuits, or acting as catalysts to trigger undesirable chemical reactions in subsequent processes, ultimately significantly reducing chip yield. According to industry standards and practices, the content of a single metal ion in electronic chemicals used in advanced processes is typically required to be controlled below 10 ppb, while high-end applications even require it to be below 1 ppb.
[0004] On the other hand, the presence of moisture is also a major concern in semiconductor processing. In photoresist systems, excessive moisture can affect the stability and coating uniformity of the photoresist, interfere with photochemical reactions, and cause line width control (CD) failure. In etching solutions, moisture can alter the etching rate and selectivity. During the cleaning process, residual moisture can cause particle re-adhesion. Therefore, the moisture content of electronic-grade polyols typically needs to be strictly controlled below 500 ppm.
[0005] However, industrial-grade polyols inevitably contain various metal ion impurities from raw materials, catalysts, equipment pipelines, and storage containers. The polyol molecule contains multiple hydroxyl groups (-OH), whose lone pairs of electrons make them natural chelating agents, capable of forming stable, soluble chelates with various metal ions. This chelating effect locks the metal ions around the polyol molecule, making them difficult to remove using traditional distillation methods.
[0006] CN114307364A discloses a method for purifying electronic-grade polyols. The polyol to be purified is passed sequentially through an anion exchange bed, a cation exchange bed, a mixed bed, and a filter via a transfer pump to obtain a polyol with a conductivity of less than 0.055 μS / cm. The anion exchange bed uses a strongly basic anion exchange resin, the cation exchange bed uses a strongly acidic cation exchange resin, and the mixed bed uses an equal mixture of a weakly acidic cation exchange resin and a weakly basic anion exchange resin. However, this method has a complex process flow, requiring multiple adsorption and filtration steps, which is detrimental to improving production efficiency.
[0007] Existing polyol purification technologies mainly include distillation, activated carbon adsorption, and traditional ion exchange. Distillation is effective for removing organic impurities with large boiling point differences, but it is largely ineffective for non-volatile metal ions or their chelates. Multi-stage distillation can reduce some impurities, but it is energy-intensive, costly, and cannot overcome physical limitations. Activated carbon adsorption is mainly used for decolorization and removal of large molecular organic matter, but its adsorption capacity and selectivity for metal ions are limited, failing to meet ppb-level requirements. Traditional ion exchange resin methods commonly use strongly acidic cation exchange resins (such as sulfonic acid-SO3H) or weakly acidic cation exchange resins (such as carboxyl-COOH) to remove some cations. However, these resins are less effective at removing metal ions that have already formed stable chelates with polyols, making it difficult to reduce the metal ion concentration to the ppb level. Furthermore, since the resin itself contains approximately 50% water, the water content in the product inevitably increases again during use.
[0008] In conclusion, developing a novel solution specifically for the purification of electronic-grade polyols has become a pressing technical challenge in the field of semiconductor materials. Summary of the Invention
[0009] The purpose of this invention is to overcome the shortcomings of existing technologies and provide a method for preparing ultra-high purity electronic-grade polyols efficiently and stably. This method aims to solve the following core technical problems: 1. How to effectively destroy or replace the stable chelates formed between polyols and metal ions to achieve deep removal of trace (ppb level) metal ions.
[0010] 2. How to achieve broad-spectrum and efficient capture of metal ions with different properties.
[0011] 3. How to remove metal ions while avoiding the introduction of large amounts of moisture, and how to control the moisture content to an extremely low level (<200 ppm) through simple and efficient subsequent processes.
[0012] To achieve the above-mentioned objectives, this invention provides a method for purifying electronic-grade polyol compounds: passing the polyol to be purified into a resin column containing functionalized chelating resin to remove metallic impurities from the polyol; the functionalized chelating resin contains one or two functional groups, namely phosphonic acid group or thiol group.
[0013] Furthermore, the preparation method of the functionalized chelating resin includes the following steps: S1: Chloromethylation reaction Cross-linked polystyrene-divinylbenzene copolymer microspheres were swollen in an inert solvent, and then chloromethylation reagent and catalyst were added to react and obtain chloromethylated polystyrene resin. S2: Functional group grafting Chloromethylated polystyrene resin is reacted with a nucleophile to covalently attach the target functional group to the resin, thereby obtaining a functionalized chelate resin. The functionalized chelate resin contains at least one functional group selected from phosphonic acid or thiol groups. The nucleophile is at least one of a trialkyl phosphite or a thiourea.
[0014] Furthermore, the functionalized chelating resin is at least one of the following: covalently grafted phosphonic acid functionalized chelating resin Resin-P, covalently grafted thiol functionalized chelating resin Resin-S, or covalently grafted phosphonic acid and thiol functionalized chelating resin Resin-PS; the covalently grafted phosphonic acid functionalized chelating resin Resin-P and the covalently grafted thiol functionalized chelating resin Resin-S are used alone or in series.
[0015] Furthermore, the reaction temperature of S1 is 20-70℃, preferably 20℃, 30℃, 40℃, 50℃, or 60℃; the reaction time is 6-12 hours. Furthermore, the inert solvent includes any one of dichloroethane, nitrobenzene, chloroform, or carbon tetrachloride; Furthermore, the chloromethylating agent includes any one of chloromethyl ether, paraformaldehyde, trioxymethylene, or 1,3-dichloroacetone; Furthermore, the catalyst includes either anhydrous tin tetrachloride (SnCl4) or anhydrous zinc chloride (ZnCl2).
[0016] Furthermore, the functionalized chelating resin is a covalently grafted phosphonic acid functionalized chelating resin Resin-P, and S2 includes the following steps: Trialkyl phosphite and chloromethyl polystyrene resin were mixed in a molar ratio of 1.5-5:1:1 and heated and stirred at 130-160°C for 4-8 hours under inert gas protection to obtain a phosphonic acid dialkyl ester functionalized resin. Subsequently, the resin was hydrolyzed with an appropriate amount of hydrochloric acid at 40-80°C for 6-24 hours to convert the phosphonate groups into phosphonic acid groups, thus obtaining the covalently grafted phosphonic acid functionalized chelating resin Resin-P. After purifying polyols using the covalently grafted phosphonic acid functionalized chelating resin Resin-P, the content of single metal impurities in the polyols was <10 ppb, and the content of both hard acid metal ions and alkali metal ions was <2 ppb.
[0017] Furthermore, the functionalized chelating resin is a covalently grafted thiol-based functionalized chelating resin, Resin-S, and S2 includes the following steps: Thiourea, chloromethylated polystyrene resin, and solvent were mixed according to a molar ratio of thiourea to chloromethyl of 1.5-5:1 and heated and stirred at 70-90°C for 4-8 hours to generate isothiourea salt intermediate. The isothiourea salt intermediate was then subjected to alkaline hydrolysis using sodium hydroxide or potassium hydroxide solution at a controlled hydrolysis temperature of 25-60°C for 8-16 hours. Finally, the resin was washed with water until neutral to obtain the covalently grafted thiol functionalized chelating resin Resin-S. The solvent is any one of anhydrous ethanol, N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide; After purifying polyols using the covalently grafted thiol functionalized chelating resin Resin-S, the content of single metal impurities in the polyols was all <20 ppb, and the content of soft acid and boundary acid metal ions was all <2 ppb.
[0018] Furthermore, the functionalized chelating resin is a covalently grafted phosphonic acid and thiol functionalized chelating resin, Resin-PS, and S2 includes the following steps: S21: Trialkyl phosphite is mixed with chloromethylated polystyrene resin and heated and stirred at 130-160°C for 4-8 hours under inert gas protection to obtain dialkyl phosphonate functionalized intermediate resin. S22: Mix the intermediate resin, thiourea and solvent, and heat under reflux at 70-90°C for 4-8 hours; the solvent is any one of anhydrous ethanol, N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide. S23: The resin obtained in S22 is subjected to acid and alkali treatment to obtain the functionalized chelating resin Resin-PS, which is covalently grafted with phosphonic acid and thiol groups. The molar ratio of trialkyl phosphite, thiourea, and chloromethyl is 0.5-4.5:0.5-4.5:1; After purifying polyols using Resin-PS, a functionalized chelating resin covalently grafted with phosphonic acid and thiol groups, the content of single metal impurities in the polyols is <1 ppb.
[0019] Furthermore, the cross-linked polystyrene-divinylbenzene copolymer microspheres are selected from one or more of Dow Chemical's Amberlite™ XAD series resins (such as XAD4, XAD16, XAD1180) or Dowex™ series resins.
[0020] Further, the polyol to be purified is passed into a resin column containing functionalized chelating resin to remove metal impurities from the polyol, and then distilled under reduced pressure to obtain a polyol with a water content of <200ppm. Furthermore, the vacuum distillation pressure is -0.05 to -0.1 MPa, and even further, the vacuum distillation pressure is -0.07 MPa, -0.08 MPa, -0.09 MPa, and -0.1 MPa; Furthermore, the vacuum distillation temperature is 60~110℃, and even further, the vacuum distillation temperature is 60℃, 70℃, 80℃, 90℃, and 100℃.
[0021] Furthermore, the length-to-diameter ratio of the resin column is 3-8, and even further, the length-to-diameter ratio of the resin column is 5, 6, or 7; Furthermore, the column flow rate is 2-20 Bv / h, and even further, the column flow rate is 2 Bv / h, 5 Bv / h, 8 Bv / h, 10 Bv / h, 15 Bv / h, and 18 Bv / h; Furthermore, the column temperature is 20-60℃, and even further, the column temperature is 25℃, 30℃, and 40℃.
[0022] Compared with the prior art, the present invention has the following significant advantages: 1. Extremely high metal removal efficiency: The functionalized resin of this invention has phosphonic acid groups and thiol groups, which can effectively capture metal ions that have formed chelates with polyols. The content of a single metal ion in the final product can be stably controlled below 1 ppb, which can meet the stringent requirements of current advanced semiconductor processes.
[0023] 2. Synergistic chelation and broad-spectrum activity: When resins are grafted with both phosphonic acid groups and thiol groups, a synergistic effect occurs. According to the hard-soft acid-base (HSAB) theory, the oxygen atom in the phosphonic acid group belongs to the hard base, and it is effective against hard acid metal ions (such as Na+). + K + Ca 2 + Fe3+ Al 3+ It has a strong affinity for ions; while the sulfur atom in the thiol group is a soft base, and has a strong affinity for soft acid metal ions (such as Cu). + Ag + Cd 2+ Hg 2+ ) and some boundary acids (such as Cu) 2+ Ni 2+ Zn 2+ This compound exhibits extremely strong binding capacity. The two groups are spatially adjacent; one group first interacts with the metal ion, altering the metal ion's coordination environment and making it easier for the other group to capture the metal ion, thus forming a more stable multidentate chelate, whose stability exceeds that of chelates formed by a single group. This gives the bifunctionalized resin a broad-spectrum and highly efficient removal capability for complex metal ion contamination systems.
[0024] 3. Integrated Solution to Metal and Moisture Problems: This invention combines efficient chelation adsorption with precision vacuum distillation. The front-end resin treatment specifically and efficiently solves the most challenging problem of trace metal ions, while the back-end vacuum distillation precisely and with low energy consumption solves the moisture problem, ultimately achieving the dual control targets of single metal ion content <1 ppb and moisture <200 ppm.
[0025] 4. Mild process, avoiding secondary pollution: The entire purification process is carried out at a relatively mild temperature (room temperature), avoiding thermal degradation of polyols. Functional groups are linked to the resin backbone through stable covalent bonds, greatly reducing the risk of organic matter leaching. The resin can be eluted and regenerated using dilute acid or chelating agent solutions such as EDTA, allowing for reuse and reducing production costs and environmental burden.
[0026] 5. Raw materials are readily available and highly operable: The starting material of this invention is commercially available PS-DVB white ball resin. The grafting reaction is a mature organic chemical reaction with a clear process route, making it easy to achieve industrial production and application. Attached Figure Description
[0027] Figure 1 This is a purification process flow diagram for the polyol compounds of this invention. Detailed Implementation
[0028] The embodiments of the present invention will be described in detail below with reference to the examples. The following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.
[0029] Example 1 (1) In a 1000 mL four-necked flask, add 100 g of commercially available Amberlite™ XAD4 resin and 400 mL of 1,2-dichloroethane, and stir magnetically to allow it to swell fully for 3 h.
[0030] (2) Add 40g of paraformaldehyde and 100g of anhydrous zinc chloride, and slowly add 150 mL of concentrated hydrochloric acid in an ice-water bath, controlling the temperature not to exceed 20℃ during the addition process.
[0031] (3) After the addition is complete, raise the temperature to 60℃ and continue stirring at this temperature for 8 hours. The reaction equation is as follows:
[0032] P-Ph represents the polystyrene skeleton.
[0033] (4) After the reaction is complete, cool to room temperature and filter to collect the resin.
[0034] (5) Wash the resin sequentially with dichloroethane, methanol and deionized water until the washing solution is neutral.
[0035] (6) The resin was washed with methanol and dried under vacuum to obtain chloromethylated resin (Resin-Cl). The chlorine content was determined to be 4.5 mmol / g by elemental analysis.
[0036] (7) Take 80g of the dried Resin-Cl resin (containing approximately 360mmol of chloromethyl) from step (6) and 195mL of triethyl phosphite (approximately 0.96mol) and add them to the reaction vessel. Under nitrogen protection, heat to 145℃ and react for 6h. The reaction equation is as follows:
[0037] (8) After the reaction is complete, cool and filter the resin, and wash the resin with anhydrous ethanol 3-5 times to remove unreacted triethyl phosphite to obtain dialkyl phosphonate resin.
[0038] (9) The obtained dialkyl phosphonate resin was placed in 500 mL of 6M hydrochloric acid solution and hydrolyzed at 60 °C for 12 h. The reaction equation is as follows:
[0039] (10) After hydrolysis, filter and collect the resin, and wash it with a large amount of deionized water until it is neutral.
[0040] (11) After washing the resin from step (10) with methanol, it was dried under vacuum to finally obtain phosphonic acid functionalized resin (Resin-P). The phosphonic acid functional group capacity was determined to be 3.8 mmol / g (the amount of substance of functional group per gram of dried resin) by acid-base titration.
[0041] (12) Select a chromatography column with an aspect ratio of 5, fill it with 60g of Resin-P resin, and rinse the resin with dilute hydrochloric acid (0.1M) and ultrapure water successively from the inlet end. Monitor the conductivity of the outlet end until the conductivity of the eluent is ≤ that of the ultrapure water.
[0042] (13) At room temperature of 25°C, the industrial grade ethylene glycol raw material to be purified was flowed through the chromatography column at a flow rate of 4 Bv / h, and 4-10 Bv of purified solution was collected.
[0043] (14) Distill the ethylene glycol purified solution collected in step (13) under reduced pressure until the conductivity of the distillate is stable and no water droplets are precipitated. Set the vacuum degree to -0.1MPa and the temperature to 60℃ to obtain electronic grade ethylene glycol product.
[0044] Example 2 Steps (1)-(6) are the same as steps (1)-(6) in Example 1.
[0045] (7) Add 80g of dried Resin-Cl (containing approximately 360mmol of chloromethyl), 96g of thiourea (approximately 1.26mol), and 400mL of ethanol to a reaction vessel, and heat under reflux at 78℃ for 5h to generate isothiourea salt intermediate. The reaction equation is as follows:
[0046] (8) After the reaction is complete, cool to room temperature, filter the resin, and wash the resin three times with ethanol.
[0047] (9) Transfer the resin from step (8) to 500 mL of 20% ethanol aqueous solution containing 60 g NaOH, and stir at 50 °C for 12 h for hydrolysis. The reaction equation is as follows:
[0048]
[0049] (10) After hydrolysis, filter and collect the resin, and wash it with deionized water until neutral.
[0050] (11) Soak the resin in step (10) in dilute hydrochloric acid (0.1M), stir for 5 minutes at room temperature to remove residual alkali, and then wash with water until neutral.
[0051] (12) The resin in step (11) was washed with methanol and dried under vacuum to obtain thiol-functionalized resin (Resin-S). Its thiol capacity was measured to be 3.8 mmol / g.
[0052] (13) Select a chromatography column with an aspect ratio of 5, fill it with 60g of Resin-S resin, and rinse the resin with dilute hydrochloric acid (0.1M) and ultrapure water successively from the inlet end. Monitor the conductivity of the outlet end until the conductivity of the eluent is ≤ that of the ultrapure water.
[0053] (14) At room temperature of 25°C, the industrial grade ethylene glycol raw material to be purified was flowed through the chromatography column at a flow rate of 4 Bv / h, and 4-10 Bv of purified solution was collected.
[0054] (15) The ethylene glycol purified solution collected in step (14) is subjected to vacuum distillation until the conductivity of the distillate is stable and no water droplets are precipitated. The vacuum degree is set to -0.1MPa and the temperature is 60℃ to obtain electronic grade ethylene glycol product.
[0055] Example 3 (1) Prepare phosphonic acid functionalized resin (Resin-P) using the same method as (1)-(11) in Example 1.
[0056] Prepare thiol-functionalized resin (Resin-S) using the same method as in Example 2 (1)-(12).
[0057] (2) Select two chromatography columns with an aspect ratio of 5, each filled with 60g of Resin-S (primary column) and Resin-P (secondary column) resin. Connect the two resin columns in series. Rinse the resin with dilute hydrochloric acid and ultrapure water successively through the inlet end of the primary column. Monitor the conductivity of the outlet end of the secondary column until the conductivity of the eluent is ≤ that of the ultrapure water.
[0058] (3) At room temperature of 25°C, the industrial grade ethylene glycol raw material to be purified is passed through the chromatography column at a flow rate of 4 Bv / h, and 4-10 Bv of purified solution is collected.
[0059] (4) The ethylene glycol purified solution collected in step (3) is subjected to vacuum distillation until the conductivity of the distillate is stable and no water droplets are precipitated. The vacuum degree is set to -0.1MPa and the temperature is 60℃ to obtain electronic grade ethylene glycol product.
[0060] Example 4 Steps (1)-(6) are the same as steps (1)-(6) in Example 1.
[0061] (7) Take 80g of Resin-Cl (containing about 360mmol of chloromethyl) and add 100mL of triethyl phosphite (about 0.49mol) into the reaction vessel. Under nitrogen protection, heat to 145℃ and react for 6h.
[0062] (8) After the reaction is complete, cool to room temperature and wash the resin three times with anhydrous ethanol to obtain a partially phosphonic acid dialkyl ester functionalized intermediate resin.
[0063] (9) The intermediate resin obtained in step (8) was added to the reaction vessel along with 61.5 g of thiourea (about 0.81 mol) and 400 mL of ethanol, and the mixture was heated and refluxed at 78 °C for 5 h.
[0064] (10) The resin obtained in step (9) is hydrolyzed with 6M hydrochloric acid at 60°C for 12 hours to convert the phosphonate group into the phosphonic acid group; then it is thoroughly washed with water until neutral; then it is treated with alkaline conditions (0.5 M NaOH) to release the thiol group, and finally washed with water until the pH is neutral.
[0065] (11) After washing and drying, a bifunctional resin (Resin-PS) was obtained. The phosphonic acid group capacity was approximately 1.95 mmol / g, the thiol group capacity was approximately 1.95 mmol / g, and the total functional group capacity was approximately 3.9 mmol / g, as determined by titration.
[0066] (12) Select a chromatography column with an aspect ratio of 5, fill it with 60g of Resin-PS resin, and rinse the resin with dilute hydrochloric acid (0.1M) and ultrapure water successively from the inlet end. Monitor the conductivity of the outlet end until the conductivity of the eluent is ≤ that of the ultrapure water.
[0067] (13) At room temperature of 25°C, the industrial grade ethylene glycol raw material to be purified was flowed through the chromatography column at a flow rate of 4 Bv / h, and 4-10 Bv of purified solution was collected.
[0068] (14) The ethylene glycol purified solution collected in step (13) is subjected to vacuum distillation until the conductivity of the distillate is stable and no water droplets are precipitated. The vacuum degree is set to -0.1MPa and the temperature is 60℃ to obtain electronic grade ethylene glycol product.
[0069] Example 5 Unlike Example 4, in step (7), the amount of triethyl phosphite added was 115 mL (about 0.57 mol), and in step (9), the amount of thiourea added was 67.5 g (about 0.89 mol). The final bifunctional resin (Resin-PS) had a phosphonic acid group capacity of about 2.10 mmol / g, a thiol group capacity of about 2.10 mmol / g, and a total functional group capacity of about 4.20 mmol / g.
[0070] The rest is the same as in Example 4.
[0071] Comparative Example 1 (1) Select a chromatography column with an aspect ratio of 5, fill it with 60g of 001x8 cation exchange resin (Lijiang Biotechnology), and rinse the resin with dilute hydrochloric acid (0.1M) and ultrapure water successively from the inlet end. Monitor the conductivity of the outlet end until the conductivity of the elution is ≤ that of the ultrapure water.
[0072] (2) At room temperature of 25°C, the industrial grade ethylene glycol raw material to be purified was flowed through the chromatography column at a flow rate of 4 Bv / h, and 4-10 Bv of purified solution was collected.
[0073] (3) The ethylene glycol purified solution collected in step (2) is subjected to vacuum distillation until the conductivity of the distillate is stable and no water droplets are precipitated. The vacuum degree is set to -0.1MPa and the temperature is 60℃ to obtain electronic grade ethylene glycol product.
[0074] The electronic-grade ethylene glycol obtained in the above examples and comparative examples was tested for impurities, and the results are shown in Table 1.
[0075] Table 1. Detection results of purified products in the examples and comparative examples.
[0076] As shown in Table 1, Resin-P (phosphonic acid group) is effective against hard acid metal ions Fe. 3+ Al 3+ Ca 2+ and alkali metal Na + These showed good removal effects, while Resin-S (thiol group) showed good removal effects on soft acids and transition metal Cu with boundary acid properties. 2+ Ag + Zn 2+ Ni 2+ The resins exhibited good removal capabilities, consistent with the predictions of the hard and soft acid-base theory. However, single-function resins are insufficient for achieving deep removal of all types of metal ions simultaneously. When different functional resins were connected in series (Example 3), the metal removal effect was improved, and the residual metal concentrations were reduced to below 2 ppb. After treatment with the bifunctional resin Resin-PS (Examples 4 and 5), the residual concentrations of all detected metal ions were reduced to below 1 ppb. Furthermore, the method provided by this invention can also efficiently remove trace amounts of moisture from ethylene glycol; by using the bifunctional resin Resin-PS, the moisture content was reduced to below 140 ppm.
[0077] The Resin-PS provided by this invention achieves ultra-efficient removal of multiple metal ions with different properties simultaneously, a uniform and deep purification effect that is difficult to achieve even when Resin-P and Resin-S are used in series. This demonstrates the synergistic effect of the two functional groups on the same resin backbone. The mechanism may be that at the microscale, the phosphonic acid group and the thiol group form a multidentate chelating group, which has a stronger bonding energy than a single group and can capture metal ions at a faster kinetic rate, thereby achieving a lower equilibrium concentration.
Claims
1. A method for purifying electronic-grade polyol compounds, characterized in that, The polyol to be purified is passed into a resin column containing functionalized chelating resin to remove metal impurities from the polyol; the functionalized chelating resin contains one or two functional groups, namely phosphonic acid group or thiol group.
2. The purification method for electronic-grade polyol compounds according to claim 1, characterized in that, The preparation method of functionalized chelating resin includes the following steps: S1: Chloromethylation reaction Cross-linked polystyrene-divinylbenzene copolymer microspheres were swollen in an inert solvent, and then chloromethylation reagent and catalyst were added to react and obtain chloromethylated polystyrene resin. S2: Functional group grafting Chloromethylated polystyrene resin is reacted with a nucleophile to obtain a functionalized chelating resin, wherein the functionalized chelating resin contains at least one functional group selected from phosphonic acid group or thiol group. The nucleophile is at least one of a trialkyl phosphite or a thiourea.
3. The purification method for electronic-grade polyol compounds according to claim 2, characterized in that, The functionalized chelating resin is at least one of the following: covalently grafted phosphonic acid functionalized chelating resin Resin-P, covalently grafted thiol functionalized chelating resin Resin-S, or covalently grafted phosphonic acid and thiol functionalized chelating resin Resin-PS; the covalently grafted phosphonic acid functionalized chelating resin Resin-P and the covalently grafted thiol functionalized chelating resin Resin-S are used alone or in series.
4. The purification method for electronic-grade polyol compounds according to claim 3, characterized in that, The reaction temperature of S1 is 20-70℃, preferably 20℃, 30℃, 40℃, 50℃, or 60℃; the reaction time is 6-12h; the inert solvent includes any one of dichloroethane, nitrobenzene, chloroform, or carbon tetrachloride; the chloromethylating agent includes any one of chloromethyl ether, paraformaldehyde, trioxymethane, or 1,3-dichloropropanone; the catalyst includes any one of anhydrous tin tetrachloride SnCl4 or anhydrous zinc chloride ZnCl2.
5. The purification method for electronic-grade polyol compounds according to claim 3, characterized in that, The functionalized chelating resin is a covalently grafted phosphonic acid functionalized chelating resin, Resin-P, S2, which includes the following steps: Trialkyl phosphite and chloromethyl polystyrene resin were mixed at a molar ratio of 1.5-5:1 and heated and stirred at 130-160°C for 4-8 hours under inert gas protection to obtain a phosphonic acid dialkyl ester functionalized resin. Subsequently, the resin was hydrolyzed with hydrochloric acid at 40-80°C for 6-24 hours to convert the phosphonate groups into phosphonic acid groups, thus obtaining the covalently grafted phosphonic acid functionalized chelating resin Resin-P. After purifying polyols using the covalently grafted phosphonic acid functionalized chelating resin Resin-P, the content of single metal impurities in the polyols was <10 ppb, and the content of both hard acid metal ions and alkali metal ions was <2 ppb.
6. The purification method for electronic-grade polyol compounds according to claim 3, characterized in that, The functionalized chelating resin is a covalently grafted thiol functionalized chelating resin, Resin-S, S2, which includes the following steps: Thiourea, chloromethylated polystyrene resin, and solvent were mixed according to a molar ratio of thiourea to chloromethyl of 1.5-5:1 and heated and stirred at 70-90°C for 4-8 hours to generate isothiourea salt intermediate. The isothiourea salt intermediate was then subjected to alkaline hydrolysis using sodium hydroxide or potassium hydroxide solution at a controlled hydrolysis temperature of 25-60°C for 8-16 hours. Finally, the resin was washed with water until neutral to obtain the covalently grafted thiol functionalized chelating resin Resin-S. The solvent is any one of anhydrous ethanol, N,N-dimethylformamide, N-methylpyrrolidone, and dimethyl sulfoxide; After purifying polyols using the covalently grafted thiol functionalized chelating resin Resin-S, the content of single metal impurities in the polyols was <20 ppb, and the content of soft acid and boundary acid metal ions was <2 ppb.
7. The purification method for electronic-grade polyol compounds according to claim 3, characterized in that, The functionalized chelating resin is Resin-PS, a functionalized chelating resin covalently grafted with phosphonic acid groups and thiol groups. S2 includes the following steps: S21: Trialkyl phosphite is mixed with chloromethylated polystyrene resin and heated and stirred at 130-160°C for 4-8 hours under inert gas protection to obtain dialkyl phosphonate functionalized intermediate resin. S22: Mix the intermediate resin, thiourea and solvent, and heat under reflux at 70-90°C for 4-8 hours; the solvent is any one of anhydrous ethanol, N,N-dimethylformamide, N-methylpyrrolidone and dimethyl sulfoxide. S23: The resin obtained in S22 is subjected to acid and alkali treatment to obtain the functionalized chelating resin Resin-PS, which is covalently grafted with phosphonic acid and thiol groups. The molar ratio of trialkyl phosphite, thiourea, and chloromethyl is 0.5-4.5:0.5-4.5:1; After purifying polyols using Resin-PS, a functionalized chelating resin covalently grafted with phosphonic acid and thiol groups, the content of single metal impurities in the polyols is <1 ppb.
8. A purification method for electronic-grade polyol compounds according to claim 2, characterized in that, The cross-linked polystyrene-divinylbenzene copolymer microspheres are selected from one or more of Dow Chemical's Amberlite™ XAD series resins (such as XAD4, XAD16, XAD1180) or Dowex™ series resins.
9. The purification method for electronic-grade polyol compounds according to claim 1, characterized in that, The polyol to be purified is passed into a resin column packed with functionalized chelating resin to remove metal impurities from the polyol. Then, it is distilled under reduced pressure to obtain a polyol with a water content of <200 ppm. The reduced pressure is -0.05 to -0.1 MPa, preferably -0.07 MPa, -0.08 MPa, -0.09 MPa, or -0.1 MPa. The reduced pressure is 60 to 110℃, preferably 60℃, 70℃, 80℃, 90℃, or 100℃.
10. The purification method for electronic-grade polyol compounds according to claim 1, characterized in that, The length-to-diameter ratio of the resin column is 3-8, preferably 5, 6, or 7; the column flow rate is 2-20 Bv / h, preferably 2 Bv / h, 5 Bv / h, 8 Bv / h, 10 Bv / h, 15 Bv / h, or 18 Bv / h; and the column flow temperature is 20-60℃, preferably 25℃, 30℃, or 40℃.
